Treating nightmares in post-traumatic stress disorder with the α-adrenergic agents clonidine and doxazosin: protocol for a phase II randomised, double-blind, placebo-controlled parallel-group study (ClonDoTrial) : protocol - Röpke, Stefan; Schoofs, Nikola; Priebe, Kathlen; Wuelfing, Felix; Roehle, Robert; Maslahati, Tolou; Stieglbauer, Katharina; Biedermann, Sarah; Schaefer, Ingo; Gallinat, Jürgen; Ethofer, Thomas; Fallgatter, Andreas J.; et al. (BMJ open, 2025)
Introduction Intrusive nightmares are a hallmark symptom of post-traumatic stress disorder (PTSD), contributing significantly to psychiatric comorbidities, impaired physical health and diminished social functioning. Currently, no pharmacological treatments are specifically approved for managing PTSD-related nightmares. However, emerging evidence suggests that adrenoceptor-targeting agents may offer therapeutic potential. Notably, clonidine and doxazosin have demonstrated efficacy in reducing PTSD-associated nightmares, as indicated by findings from open-label studies and small randomised controlled trials. - Methods and analysis This study is a multicentre, double-blind, randomised (1:1:1), placebo-controlled, parallel-group interventional trial. A total of 189 eligible patients will be randomly assigned to receive clonidine, doxazosin or placebo, with a once-daily oral dose administered at bedtime for 10 weeks. The primary efficacy endpoint is the Clinician-Administered PTSD Scale B2 score at week 10, which measures the frequency and intensity of nightmares. Secondary efficacy endpoints include other PTSD-specific symptoms. Additionally, the safety of clonidine and doxazosin will be assessed. - Ethics and dissemination The study was approved by the Ethics Committee of the State of Berlin (Ethik-Kommission des Landes Berlin) (Reference: 21-683-Haupt-IV E 13), on 14 March 2022 and by the relevant federal authority, the Bundesinstitut für Arzneimittel und Medizinprodukte, reference 4044931. The study was conducted in accordance with the relevant guidelines and regulations. The study results will be published in peer-reviewed journals and presented at both national and international conferences. - Trial registration number NCT05360953, EudraCT 2021-000319-21.